2021
DOI: 10.1017/dmp.2021.305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Natural Hazards on Older Adult Health: Lessons Learned From Hurricane Maria in Puerto Rico

Abstract: Objective: With natural hazards increasing in frequency and severity and global population aging, preparedness efforts must evolve to address older adults’ risks in disasters. This study elucidates potential contributors to the elevated older adult mortality risk following Hurricane Maria in Puerto Rico through an examination of community stakeholder preparedness, response, and recovery experiences. Methods: In April 2018, qualitative interviews (n = 22) were conducted with stakeholders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Further, Acosta and Irizarry (2018) found that there was a prolonged increase in the death rate for circulatory, endocrine and respiratory causes of deathwhile the death rate increased by 74% immediately following the storm, a 22% increase was sustained for eight months post-hurricane. Similar to the findings by Acosta and Irizarry (2018), our research team from the [UNI-VERSITY] estimated an overall excess mortality of 2975 from Hurricane Maria between September 2017 and February 2018 [82,83], with older adults and residents of municipalities with lower SES experiencing disproportionate excess deaths and elevated death rates for longer during that time period [82,84]. Based on these findings, this investigation sought to examine Hurricane Maria's impacts in ten lower SES municipalities in Puerto Rico with varying characteristics to understand the nature of these impacts and community experiences of supporting individuals with NCD management in these post-hurricane contexts.…”
Section: Introductionsupporting
confidence: 75%
“…Further, Acosta and Irizarry (2018) found that there was a prolonged increase in the death rate for circulatory, endocrine and respiratory causes of deathwhile the death rate increased by 74% immediately following the storm, a 22% increase was sustained for eight months post-hurricane. Similar to the findings by Acosta and Irizarry (2018), our research team from the [UNI-VERSITY] estimated an overall excess mortality of 2975 from Hurricane Maria between September 2017 and February 2018 [82,83], with older adults and residents of municipalities with lower SES experiencing disproportionate excess deaths and elevated death rates for longer during that time period [82,84]. Based on these findings, this investigation sought to examine Hurricane Maria's impacts in ten lower SES municipalities in Puerto Rico with varying characteristics to understand the nature of these impacts and community experiences of supporting individuals with NCD management in these post-hurricane contexts.…”
Section: Introductionsupporting
confidence: 75%
“…Much research on disasters and older populations have shown their reliance on social capital in times of crisis [ 28 , 32 , 33 , 34 , 35 , 36 , 37 ]. In turn, increases in social isolation and loneliness amongst older adults have been studied extensively in recent years as negatively effecting overall health after disasters [ 38 , 39 ]. The strengthening of social infrastructure is something that care teams like home health agencies and local and regional policy makers must consider when ensuring older, vulnerable populations are safe and cared for during and after future disasters.…”
Section: Discussionmentioning
confidence: 99%
“…The departure of hundreds of thousands of people from Puerto Rico to the U.S. mainland was caused, at least in part, by the island’s mounting debt and the U.S. government’s austerity measures that were intended to reduce that debt (Colón, 2015). During this time, many adults experienced unmet needs that contributed to declining physical and emotional health, inadequate noncommunicable disease management, social isolation, financial strain, and excess morbidity and mortality (Andrade et al, in press). Many Puerto Ricans were also troubled by what they viewed as corruption within the island’s government, decaying infrastructure, and deteriorating manufacturing and energy sectors (LeBrón, 2017; O’Neill-Carrillo & Rivera-Quiñones, 2018; Villanueva, 2019).…”
Section: Crisis Migration and Cultural Stress Among Hurricane Survivorsmentioning
confidence: 99%